Rural demography, public services, and land rights in Africa: A village-level analysis in Burkina Faso - McMillan, Margaret S.; Masters, William A.; Kazianga, Harounan (International Food Policy Research Institute, 2012)
This paper uses historical census data from Burkina Faso to characterize local demographic pressures associated with internal migration into river valleys after onchocerciasis eradication, combined with a new survey of village elders to document change over time and differences across villages in local public goods provision, market institutions, and land use rights. We hypothesize that higher local population densities are associated with more public goods and with a transition from open-access to regulated land use. Controlling for province or village fixed effects, we find that villages’ variance in population associated with proximity to rivers is closely correlated with higher levels of infrastructure, markets, and individual land rights, as opposed to familial or communal rights. Responding to population growth with both improved public services and private property rights is consistent with both scale effects in public good provision and changes in the scarcity of land.